2022
DOI: 10.1039/d1sc05988b
|View full text |Cite
|
Sign up to set email alerts
|

Can a Wanzlick-like equilibrium exist between dicoordinate borylenes and diborenes?

Abstract: Boron chemistry has experienced tremendous progress in the last few decades, resulting in the isolation of a variety of compounds with remarkable electronic structures and properties. Some examples are the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 96 publications
0
3
0
Order By: Relevance
“…11 The single base-stabilised borylene can react with many unreactive small molecules like N 2 . Boron centers were introduced with various Lewis(two-electron)donor and anionic substituents such as NHCs, Dur, SiMe 3 , and so on by Felipe et al 12 In addition, two borylene fragments, [(CAAC)-DurB] or [(CAAC)TipB] 2 (m 2 -N 4 K 2 ) (Tip. 2,4,6-triisopropylphenyl), could be bridged by N2 or N4 chains.…”
Section: Introductionmentioning
confidence: 99%
“…11 The single base-stabilised borylene can react with many unreactive small molecules like N 2 . Boron centers were introduced with various Lewis(two-electron)donor and anionic substituents such as NHCs, Dur, SiMe 3 , and so on by Felipe et al 12 In addition, two borylene fragments, [(CAAC)-DurB] or [(CAAC)TipB] 2 (m 2 -N 4 K 2 ) (Tip. 2,4,6-triisopropylphenyl), could be bridged by N2 or N4 chains.…”
Section: Introductionmentioning
confidence: 99%
“…Following Bertrand’s and Robinson’s landmark syntheses of the first metal-free borylene and diborene, respectively, , the past decade has seen a surge in the reports of doubly base-stabilized tricoordinate LL′(R)­B: borylenes and L­(R)­BB­(R)­L diborenes. Stable L­(R)­B: dicoordinate borylenes, however, remain limited to a few examples stabilized by the push–pull interaction of a π-donating amino substituent and a π-accepting carbene ligand ( I , Scheme a). Due to the linear geometry, steric shielding, and electronic saturation of their boron center, these species do not dimerize to the corresponding diaminodiborenes. Thus far, attempts to generate dicoordinate borylenes in situ by the photolytic or thermal abstraction of a labile donor ligand (e.g., CO, PMe 3 ) from a tricoordinate borylene have systematically led to intramolecular C–H or C–C activation reactions rather than dimerization. Experimental and computational studies on the only known formal borylene-diborene L­(R)­B:/L­(R)­BB­(R)­L pair, tetrameric cyanoborylene I and cyanodiborene II (Scheme a), showed that these two species do not interconvert owing to the preferred self-stabilization of I through B–CN–B linkages. , The fact, however, that certain LBRX 2 (X = halide) precursors can be reduced either to a tricoordinate borylene (or borylene equivalent) in the presence of a second base L′ or to a diborene in the absence thereof suggests the feasibility of borylene-to-diborene dimerization. The reduction of an NHC-stabilized cymantrenylborane, for example, yields either the bis­(NHC)­borylene III , stabilized by its boratafulvene resonance form, or the corresponding diborene IV , depending on the nature of the reaction solvent (Scheme b) .…”
Section: Introductionmentioning
confidence: 99%
“…61−65 Experimental and computational studies on the only known formal borylene-diborene L(R)B:/L(R)B� B(R)L pair, tetrameric cyanoborylene I and cyanodiborene II (Scheme 2a), showed that these two species do not interconvert owing to the preferred self-stabilization of I through B−CN−B linkages. 66,67 The fact, however, that certain LBRX 2 (X = halide) precursors can be reduced either to a tricoordinate borylene (or borylene equivalent) in the presence of a second base L′ or to a diborene in the absence thereof suggests the feasibility of borylene-to-diborene dimerization. The reduction of an NHC-stabilized cymantrenylborane, for example, yields either the bis(NHC)borylene III, stabilized by its boratafulvene resonance form, or the corresponding diborene IV, depending on the nature of the reaction solvent (Scheme 2b).…”
Section: ■ Introductionmentioning
confidence: 99%